Understanding Concepts in Current Psychology - Akimova, Nataliia (Psychological Prospects Journal, 2018)
The modern psychological views on the problem of understanding are generalized in the article. It is noted that the specificity of understanding was studied in theosophy and philosophy for centuries. Recognition of the important role of the subject in the process of understanding contributed to the fact that this problem also became the subject of psychology. The primary objective of the article is to analyze and to systematize modern theories of understanding, taking into account the scientific tradition and new trends. Different methods were used for this purpose: deductive and inductive methods, analysis and synthesis, generalization, systematization and modeling as well as some interpretive methods that are based on specific principles of systemic, activity, cognitive and organizational approaches The conclusion is made as a result of systematization of the achievements of these approaches. It is concluded that six approaches to the interpretation of understanding can be accented in modern psychological literature. They are understanding as knowledge (a certain form of knowledge, process and result of cognition), understanding as comprehension (collapse and reproduction of meanings that are in all, we may only found and restored them), understanding as interpretation (matching of interpretations), understanding as a process of solving tasks (the transit process from one stage to another, from recognition to the generic concept, then the meaning of the specific concept, then the explanation), understanding as the inclusion of new knowledge in the subject’s experience (enrichment of experience, accumulation of knowledge), understanding as awareness (a function of consciousness that includes thinking, feeling, experience, relationships, etc.). In general, understanding is a complex psychic process that begins with perception and thinking, then includes other cognitive processes and the emotional and volitional sphere, reaching the level of consciousness, realized in the sense, establishing links with values and emotions. Prerequisites for understanding are sufficient prior experience and knowledge.